2020
DOI: 10.1103/physrevb.102.165109
|View full text |Cite
|
Sign up to set email alerts
|

Proton mobility in metallic copper hydride from high-pressure nuclear magnetic resonance

Abstract: The atomic and electronic structures of Cu 2 H and CuH have been investigated by high-pressure nuclear magnetic resonance spectroscopy up to 96 GPa, X-ray diffraction up to 160 GPa, and density functional theory-based calculations. Metallic Cu 2 H was synthesized at a pressure of 40 GPa, and semimetallic CuH at 90 GPa, found stable up to 160 GPa. For Cu 2 H, experiments and computations show an anomalous increase in the electronic density of state at the Fermi level for the hydrogen 1s states and the formation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…1 H) nuclei. Contrarily, moderate dynamic averaging of hydrogen NMR resonances is a well established diagnostic tool to identify locally restricted low amplitude motions and has even been employed to determine hydrogen diffusivities in diamond anvil cell based research 33 . This minimum indicates the point of maximum hydrogen diffusivity within the H-bond, leading to a striking conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…1 H) nuclei. Contrarily, moderate dynamic averaging of hydrogen NMR resonances is a well established diagnostic tool to identify locally restricted low amplitude motions and has even been employed to determine hydrogen diffusivities in diamond anvil cell based research 33 . This minimum indicates the point of maximum hydrogen diffusivity within the H-bond, leading to a striking conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…YH 3 as well as the recently discovered tetragonal phase tI140 of sulfur polyhydride (H 6±δ S 5 ) (δ ≈ 0.4) by Laniel et al [31]. DAC preparation for iron and copper hydrides are described elsewhere [28,32]. Pressure cells for sulfur (S-cell) and yttrium (Y-cell) hydrides were prepared in a similar fashion.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we attribute the signal at 263 ppm to YH 3 . The presence of weaker signals in addition to the expected signals of YH 2 and YH 3 in the highresolution Lee-Goldburg spectrum suggests the formation of either YH x phases with slightly higher hydrogenation 57 or possible metallic ternary compounds formed by incorporation of carbon stemming from the paraffin hydrogen reservoir or from the diamond anvils. Further investigation of the reaction dynamics as well as supporting DFT-based computations will hopefully help to identify these additional signals and will be presented at a later stage.…”
Section: Phase Heterogeneity In Metal Hydridesmentioning
confidence: 98%
“…NMR spectroscopy could yield information about the electronic and dynamic properties of the hydrogen subsystems in these compounds. Our first experiments on iron 11 as well as copper hydrides 57 demonstrated that NMR can be used to detect hydrogen systems associated to metallic metal hydride phases synthesised at high-P under laser heating conditions and that in combination with density-function-theory (DFT) based electronic structure calculations different coexisting hydrides can be distinguished from their electronic properties, if signals do not strongly overlap 57 .…”
Section: Phase Heterogeneity In Metal Hydridesmentioning
confidence: 99%